2006
DOI: 10.1007/s11240-005-9062-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro plant regeneration of Arachis correntina (Leguminosae) through somatic embryogenesis and organogenesis

Abstract: In vitro protocols for plant regeneration of Arachis correntina through both somatic embryogenesis and organogenesis were developed using immature leaves as explants. Morphologically normal somatic embryos were obtained on culture media composed of 20.70 or 41.41 lM picloram (PIC) with the addition of 0.044 lM 6-benzylaminopurine (BA), resulting in a 33 and 24% of conversion into plants, respectively. The source of explants and the developmental stage of the leaves had a marked effect on somatic embryogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Regeneration through rhyzogenesis (percentage of regeneration was 10%) was observed only in calli grown on triple concentration of nanoparticles (Table 2). Calli growing on medium without C nanoparticles formed embryos with better quality: higher number of normal embryos in globular stages were detected (Salaj et al, 2005;Vidoz et al, 2006;Chakravarthi et al, 2010). Calli grown on medium with C nanoparticles, formed numerous abnormal embryos with different variations like embryous fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration through rhyzogenesis (percentage of regeneration was 10%) was observed only in calli grown on triple concentration of nanoparticles (Table 2). Calli growing on medium without C nanoparticles formed embryos with better quality: higher number of normal embryos in globular stages were detected (Salaj et al, 2005;Vidoz et al, 2006;Chakravarthi et al, 2010). Calli grown on medium with C nanoparticles, formed numerous abnormal embryos with different variations like embryous fusion.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, this approach was successfully used to recover plants from embryonic axes, embryonary leaflets and cotyledons of several accessions from sections Extranervosae, Heteranthae, Caulorrhizae, Erectoides, Procumbentes and Arachis, which had lost germinative capacity (Gagliardi et al 2000;Pacheco et al 2007a). In addition, some authors have reported the use of seed explants for the induction of somatic embryogenesis (Pacheco et al 2007b;Rey and Mroginski 2006;Sellars et al 1990;Vidoz et al 2006). …”
Section: Seed Explantsmentioning
confidence: 99%
“…The main growth regulator used to induce organogenesis from these explants is BAP, alone or in combination with auxins (Gagliardi et al 2000;Mansur et al 1993;Pacheco et al 2007a;Pittman et al 1983Pittman et al , 1984Vidoz et al 2006). However, Rey and Mroginski (2006) and Vidoz et al (2006) reported the induction of somatic embryogenesis from embryonic leaflets of A. pintoi and A. correntina in response to combinations of BAP and picloram. In addition, Pacheco et al (2007b) observed the formation of friable embryogenic calli from explants of A. archeri, A. porphyrocalix and A. appressipila, in response to the same BAP concentrations that induced indirect organogenesis in species of other sections.…”
Section: Embryonic Leafletsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good regeneration protocol is an essential prerequisite for conservation as well as genetic manipulation. Earlier, explants like protoplasts, petiole, cotyledon, embryo axis, stem base callus and leaves (Li et al 1993;Rani and Reddy 1996;Gagliardi et al 2000;Laxmi and Giri 2003b;Mroginski et al 2004;Vidoz et al 2006;Pacheco et al 2008) were used to achieve morphogenesis in vitro with limited success in wild species of Arachis. Cultivated peanut appears to be an easy system for in vitro culture.…”
Section: Introductionmentioning
confidence: 99%